A brief xerostomia inventory for young adults - Benjamin W. Chaffee; Elizabeth T. Couch; Caroline Shiboski; Lindsay Till Hoyt; Alison K. Cohen; Jing Cheng (PLoS ONE, 2026)
Objective Xerostomia (dry mouth) is a common condition that negatively impacts life quality for adults of all ages. Yet, xerostomia has primarily been studied among older adults and populations at high risk of dry mouth, with no widely-available self-reported instrument to assess xerostomia accurately among younger populations. This study aimed to develop a brief xerostomia assessment tool specifically designed for young adults. Methods Students ages 18–24 at two California (USA) public universities (N = 278) completed a cross-sectional survey that included a 14-item xerostomia inventory, including new items and items previously tested among older adults. Using exploratory factor analysis and item response theory analysis, the inventory was reduced to a 5-item scale. Psychometric properties of the 5 items were examined. As further validity checks, associations were explored between scale sum scores and other oral health conditions and potential xerostomia risk indicators. Results A proposed 5-item Young Adult version of the Shortened Xerostomia Inventory (SXI-Y) had favorable psychometric properties in this population, including excellent internal consistency (Cronbach alpha = 0.817) and strong correlation with a global measure of dry mouth (polychoric correlation = 0.711). SXI-Y sum scores (overall mean = 7.3; median = 6; range: 5–18) were higher (indicating more severe xerostomia) among participants who reported gum bleeding, oral pain, and halitosis and those taking prescription medications, using nicotine or cannabis, and reporting less sleep and more stress. Conclusions In this study, a xerostomia measure tailored for young adults demonstrated stronger internal consistency and retained more item-level information than an earlier tool developed for older adults. Associations of xerostomia with sleep and stress merit further investigation, as does instrument testing in additional study populations.